Structure-function analysis of the SaPIbov1 replication origin in Staphylococcus aureus - Ubeda, Carles; Tormo-Mas, María A.; Penadés, José R.; Novick, Richard P. (2017)
The SaPIs and their relatives are phage satellites and are unique among the known bacterial pathogenicity islands in their ability to replicate autonomously. They possess a phage-like replicon, which is organized as two sets of iterons arrayed symmetrically to flank an AT-rich region that is driven to melt by the binding of a SaPI-specific initiator (Rep) to the flanking iterons. Extensive deletion analysis has revealed that Rep can bind to a single iteron, generating a simple shift in a gel mobility assay; when bound on both sides, a second retarded band is seen, suggesting independent binding. Binding to both sites of the on is necessary but not sufficient to melt the AT-rich region and initiate replication. For these processes, virtually the entire origin must be present. Since SaPI replication can be initiated on linear DNA, it is suggested that bilateral binding may be necessary to constrain the intervening DNA to enable Rep-driven melting. (C) 2012 Elsevier Inc. All rights reserved.